Market versus policy Europeanisation: has an imbalance grown over time? - Francesco Papadia; Leonardo Cadamuro (Bruegel, 2020)
This Policy Contribution tests the hypothesis that an imbalance has grown in Europe over the last few decades because markets have integrated to a greater extent than Europeanlevel policymaking, potentially creating difficulties for the democratic process in managing the economy. This hypothesis has been put forward by several authors but not so far tested empirically. To evaluate the process of European market integration - or market Europeanisation - over the last few decades, we assess intra-European trade and intra-European capital flows. Any estimate of policy integration, or Europeanisation, meanwhile, is fraught with difficulties and only proxies can be measured. Our preferred proxy is the number of employees of the European institutions and agencies relative to the aggregate number of public employees in national administrations in the European Union. The assumption is that European public employees generate, implement and oversee European policies and thus their relative number is a proxy for the development of European policies. An alternative indicator of policy Europeanisation is the relative frequency of European Union news in major national media outlets, as a proxy for the relevance to the public of European policies. Our results show that, measured by our proxies, policy Europeanisation has developed more rapidly than market Europeanisation, measured on the basis of both trade and capital flows. It is however also noted that the relative number of public employees has outpaced the relative frequency of European Union news in the media, possibly indicating a technocratic slant in policy Europeanisation. Further research could test the robustness of our results, in particular by using other measures of policy Europeanisation, such as the impact of European legislation on national laws and regulations.
Keywords: 330